A Critical Analysis Criminal Justice System Relating to Cyber-Crime: Adapting the Criminal Justice System to Address Cyber-Crime (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The role of criminal justice system in other traditional crimes they are same role is cyber-crime related crimes. The biggest difference between traditional crime and cyber-crime is the use of modern technology such as computers and the Internet to commit crimes. Due to which there is a need to change the nature of crime in the way of conducting crime related investigation. In the present time, it has become a necessity to change the criminal justice system according to cybercrime.